控制装置、控制方法以及记录介质 (2024)
本发明提供一种控制装置、控制方法以及记录介质，即使在因外界干扰等的影响导致响应发生了变化的情况下，也能够将过渡状态下多个控制对象的控制量的分布控制为所期望的分布。多个控制部件包含控制量相对于目标值的响应速度最慢的第一控制部件、以及第一控制部件以外的第二控制部件。控制装置包括：预测部件，用于在每个控制周期，使用表示与第一控制部件对应的第一控制对象的动态特性的第一模型，来预测第一控制对象的未来控制量；以及生成部件，根据未来控制量，生成与第二控制部件对应的第二控制对象的未来目标值。第二控制部件基于未来目标值来决定对第二控制对象的操作量。 A plurality of control means include a first control means and a second control means other than the first control means, the first control means showing the slowest response speed of a control amount with respect to a target value. A control device is provided with: a prediction means for predicting a future control amount for a first control subject by using a first model indicating dynamic characteristics of the first control subject corresponding to the first control means for each control period; and a generation means for generating a future target value of a second control subject corresponding to the second control means from the future control amount. The second control means determines an operation amount for the second control subject